IDENTITY PROBLEM OF AFRICAN AMERICANS AS SEEN IN LANGSTON HUGHES' "I, TOO" AND PAUL LAURENCE DUNBAR'S "WE WEAR THE MASK" - Emilia Tetty Harjani; Sri Saraswati (Conscientia, 2022)
Abstract This study is about the identity problem of African Americans in Langston Hughes’ “I, Too” and Paul Dunbar’s “We Wear the Mask”. The objectives of the study are to find out the portrayal of identity problem in the poems and the poets’ attitude and world view. The study employs sociological approach and Pricilla B.P Clark’ literary sociology as the theory and library research as the method of collecting data. The results show that the racism faced by African Americans in America and their self-identification and position as American citizens have put them in identity problem. Meanwhile, the poets, though in different attitudes, have shown their optimism that the African Americans will not face racial discrimination and gain equality in the future.